An ultra-sharp artificial stone cutting saw blade and a method for manufacturing the same
Patent Information
- Application Number
- CN202611414899.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-12
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]为了解决现有技术中切割阻力大、易崩边、排屑差和焊接难度大的问题,本申请提供一种超锋利人造石材切割锯片及其制备方法
1、由于本申请采用锋利工作外层、高强缓冲中间层和易焊过渡底层的烧结体作为切割刀头,高强缓冲中间层内添加稀土元素铈,具有优异的阻尼性能,能有效阻断振动能量向基体传递,改善切割声学环境;易焊过渡底层以铜为基体,完全摈弃铁、钴,并添加锡、镍和锌,该体系表面能低,能与银基钎料形成良好的冶金互溶,降低湿润角,使焊料自动铺展并渗入毛细缝隙,提高焊接牢度,延长锯片使用寿命。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This application relates to the field of cutting tools for superhard materials, and more specifically, it relates to an ultra-sharp artificial stone cutting saw blade for efficient and non-destructive cutting of high-hardness and high-brittle artificial stone (such as quartz stone, slab stone, and microcrystalline stone) and its preparation method. Background Technology
[0002] Artificial stone (including large-format slabs and high-density quartz stone) is widely used in architectural decoration, kitchen countertops, and bathroom panels due to its beautiful texture, wear resistance, and stain resistance. As artificial stone develops towards larger scales and higher densities, its hardness and brittleness have significantly increased, placing higher demands on cutting tools. Diamond saw blades, with their advantages of high cutting efficiency, high cutting quality, and low processing cost, are widely used in cutting various non-metallic hard and brittle materials such as stone, building construction, and glass and ceramics.
[0003] However, traditional diamond saw blades still have the following significant drawbacks when cutting modern high-hardness artificial stone: 1. Simple blade structure, high cutting noise and easy edge chipping: Due to narrow kerf, poor heat dissipation, and uneven force distribution, traditional diamond saw blades often experience thermal and axial deformation during operation, generating vibration. If the vibration frequency is close to the external excitation frequency, resonance will occur, resulting not only in high noise but also in blade wobble leading to a wider kerf, skewed kerf, reduced surface quality, and even edge chipping. 2. Random distribution of diamonds in the matrix, uneven impact leading to corner chipping: Most traditional diamond saw blades use a three-dimensional mixing process of diamond-coated granulation and pre-alloyed matrix powder. The diamond particles are randomly distributed in the matrix, easily resulting in agglomeration or scarcity, leading to low effective diamond utilization, poor blade sharpness, and short service life. Moreover, due to the uneven impact of individual diamonds on the stone, it is very easy for chipping to occur at the cut edges of artificial stone. 3. Unstable welding strength of the cutting head: For multi-layer composite cutting heads, the material composition of the bottom matrix has a significant impact on the subsequent welding process. If the content of elements such as iron and cobalt in the bottom matrix is too high, it will significantly increase the difficulty of subsequent high-frequency silver brazing, leading to the risk of incomplete welding or tooth loss, and thus causing poor cutting problems such as edge chipping.
[0004] In summary, existing diamond saw blades have significant shortcomings in terms of matrix structure, diamond distribution, and blade welding, making it difficult to meet the precision cutting requirements of modern large-format slabs and high-density quartz and other hard and brittle materials. Therefore, there is an urgent need to develop an ultra-sharp artificial stone cutting saw blade that can effectively reduce cutting resistance, prevent edge chipping, improve chip removal performance, and has high welding reliability. Summary of the Invention
[0005] To address the problems of high cutting resistance, easy chipping, poor chip removal, and difficult welding in existing technologies, this application provides an ultra-sharp artificial stone cutting saw blade and its preparation method.
[0006] In the first aspect, this application provides an ultra-sharp artificial stone cutting saw blade, which adopts the following technical solution: An ultra-sharp artificial stone cutting saw blade includes a silent base and a plurality of cutting heads uniformly welded to the outer edge of the silent base. The silent base is a sandwich structure of special steel sheet-copper alloy sheet-special steel sheet. The cutting head is a sintered body consisting of a weldable transition bottom layer, a high-strength buffer intermediate layer, and a sharp working outer layer. The weldable transition bottom layer, the high-strength buffer intermediate layer, and the sharp working outer layer are arranged sequentially from the inside to the outside along a direction perpendicular to the surface of the silent substrate. The weldable transition bottom layer is in contact with the surface of the silent substrate. The solderable transition underlayer comprises, by weight percentage, 70-75% copper powder, 10-15% tin powder, 5-10% nickel powder, and 10% zinc powder; The high-strength buffer intermediate layer comprises, by weight percentage, 20-30% copper powder, 10-19.5% nickel powder, 0.5% cerium, and the remainder is iron powder; The sharp working outer layer is made of working layer matrix powder and diamond particles. The working layer matrix powder, by mass percentage, includes 40-50% copper powder, 10-15% tin powder, 15-20% cobalt powder, 10-15% nickel powder, 2-5% titanium powder, and 5-8% tungsten carbide.
[0007] By adopting the above technical solution, a sandwich structure formed by special steel sheets, copper alloy sheets and special steel sheets is used as the matrix. Copper alloy has damping characteristics, and its damping characteristics are much higher than those of steel. The copper alloy sandwiched between two layers of special steel sheets can absorb and dissipate vibration energy, thereby reducing cutting noise. In addition, the copper alloy sheet interlayer can also play a role in dissipating cutting heat.
[0008] The easy-to-solder transition underlayer uses copper as the base, supplemented with tin, nickel, and zinc, while eliminating iron and cobalt. Traditional underlayers containing high amounts of iron and cobalt are prone to oxidation at high brazing temperatures, forming a thick oxide film that increases the surface tension between the liquid silver solder sheet and the substrate. In contrast, the copper, tin, nickel, and zinc in this application have low surface energies, allowing for good metallurgical miscibility with silver-based brazing filler metal, significantly reducing the wetting angle and enabling the solder to spread and penetrate automatically. The addition of zinc deoxidizes and activates the interface, widening the allowable temperature range for high-frequency induction brazing, reducing the risk of overheating or incomplete penetration, fundamentally eliminating the risk of incomplete soldering and tooth breakage, and resulting in low residual stress after welding, making it less prone to cracking at the top of the base tooth.
[0009] The high-strength buffer interlayer uses iron powder as a framework to provide rigid support, combined with a solid solution formed by copper and nickel that exhibits excellent grain boundary dissipation properties. Trace amounts of highly interfacially active cerium are introduced to hinder grain growth within the Fe-Cu-Ni solid solution, refining the grains and crystallizing grain boundaries, thus significantly improving the material's damping characteristics under alternating stress. When cutting brittle stone and generating high-frequency micro-vibrations, the interlayer can absorb and dissipate vibrational energy through grain boundary slip, effectively blocking the transmission of high-frequency vibrations to the matrix. No diamond is added to the interlayer to ensure its density and structural uniformity, avoiding stress concentration points caused by diamond interfaces and ensuring its reliability as a buffer pad.
[0010] The working layer matrix powder of the sharp working outer layer is based on copper powder, with the addition of cobalt and nickel to improve high-temperature strength; at the same time, titanium and tungsten carbide are introduced to form hard symbiotic wear-resistant particles without affecting the wetting of diamond particles; the above-mentioned combination of multiple components makes the matrix have better holding force on diamond particles, which can firmly hold diamond particles and can also be micro-peeled off synchronously as diamond particles become dull, ensuring that there are always sharp new diamonds exposed on the cutting surface, and significantly reducing cutting resistance.
[0011] Therefore, when the bottom layer, middle layer and outer layer are combined by hot pressing and sintering to form a complete cutting head, and then brazed to the substrate, the resulting saw blade can reduce cutting resistance, increase cutting speed, and prevent the substrate from swaying violently. The cut is straight and the width is uniform, and the edge of the cut is smooth without gaps. At the same time, the bottom layer has good wettability with the silver solder sheet and high welding strength, while the middle layer can physically absorb high-frequency micro-vibrations and reduce cutting noise.
[0012] Preferably, the thickness ratio of the easy-to-solder transition layer, the high-strength buffer intermediate layer, and the sharp working outer layer is 1:2:7.
[0013] By adopting the above technical solution, the sharp working outer layer is used to directly cut the stone. It is the consumable layer with the largest thickness and the most orderly arranged layers of diamond particles. The sufficient thickness ensures that there are enough cycles of new and old replacement, which extends the saw blade life and prevents the blade from becoming dull and stopping after a short cutting time. The high-strength buffer intermediate layer is used to absorb high-frequency vibration and block stress transmission. If the intermediate layer is too thick, although the vibration reduction effect is good, it will compress the outer working layer space, resulting in a decrease in saw blade life. Moreover, the sharp outer working layer has high hardness and is easy to weld. The transition layer is a soft copper base, and the hardness difference between the two is huge. The high-strength buffer intermediate layer serves as a mechanical transition zone to avoid interface stress concentration caused by abrupt changes in the mechanical properties of the inner and outer layers and to prevent interlayer peeling.
[0014] The easily weldable transition layer connects the saw blade head to the base body, achieving high-strength welding. The above-mentioned proportion is sufficient to ensure that the solder fully spreads on the surface of the base layer and penetrates into the capillary gaps during brazing, achieving the target weld strength. This thickness ratio enables the saw blade to exhibit excellent performance such as low noise, smooth cutting, zero chipping, and long service life.
[0015] Preferably, the volume fraction concentration of the diamond particles in the sharp working outer layer is 10-15%.
[0016] By adopting the above technical solution, the concentration of diamond particles in the sharp working outer layer, the particle size of the diamond particles, and the three-dimensional orderly arrangement of the diamond particles are coordinated to ensure that each diamond particle is surrounded by a sufficiently thick working layer of matrix powder. This ensures that each diamond particle can effectively exit the cutting edge and bear equal force during cutting, achieving zero edge chipping. Furthermore, the matrix material has sufficient width and bending strength to prevent the diamonds from falling off prematurely due to excessive wear of the matrix before they become dull, significantly improving the utilization rate of the diamonds. Under the orderly arrangement, the appropriate volume fraction ensures that a sufficient number of diamond particles are distributed per unit area, ensuring that the saw blade maintains a constant exit height throughout its entire lifespan, resulting in a light and smooth cutting motion. At the same time, it gives the saw head optimal chip removal and flow capacity, avoiding the situation where the volume fraction is too low, causing the individual diamond particles to bear excessive cutting force and break or be pulled out prematurely. It also prevents the volume fraction from being too high, resulting in the matrix material between the diamond particles being too thin, which weakens the holding force on individual particles.
[0017] Preferably, a silicon carbide layer and a cerium oxide layer are sequentially deposited on the surface of the diamond particles.
[0018] By adopting the above technical solution, diamond particles with silicon carbide and cerium oxide layers deposited sequentially on the surface can provide extremely high hardness. Cerium oxide is a highly efficient polishing agent that can perform chemical mechanical polishing, reducing surface roughness and obtaining high surface quality. The silicon carbide and cerium oxide layers can effectively isolate oxygen and water in the processing environment, inhibiting further graphitization of diamond at high temperatures, while delaying diamond oxidation and corrosion. In addition, the silicon carbide and cerium oxide layers can serve as transition layers, improving the wettability between diamond and matrix powder, increasing the mechanical holding force of the matrix on the diamond, reducing premature abrasive shedding, and extending the tool life. At the same time, the protected diamond can maintain its sharpness for a longer period of time, ensuring stable and efficient cutting.
[0019] Preferably, the method for sequentially depositing a silicon carbide layer and a cerium oxide layer on the surface of the diamond particles includes the following steps: Diamond particles were placed in a vacuum sintering furnace for surface graphitization treatment. The temperature was first raised to 800°C at a rate of 30°C / min, then raised to 1500°C at a rate of 20°C / min, and then raised to 1600°C at a rate of 10°C / min. The temperature was then held under vacuum without pressure for 15 minutes to obtain diamond / graphite composite particles. Diamond / graphite composite particles were placed in a graphite cavity filled with silicon powder and fixed 8 mm above the silicon powder. The graphite cavity was then moved into a vacuum furnace and heated to 1700°C at a heating rate of 8°C / min. The vacuum degree was set to 1 Pa and held for 30 min. The furnace was then cooled to room temperature to obtain diamond particles with deposited silicon carbide. Deionized water and anhydrous ethanol were mixed in a 1:1 mass ratio, diamond particles deposited with silicon carbide were added, the mixture was stirred for 30 min and sonicated for 120 min to obtain a suspension. Cerium nitrate was added to the suspension, hexamethylenetetramine solution was added dropwise, the pH was adjusted with sodium hydroxide solution, and the mixture was heated and stirred in a water bath at 75-80℃ for 2 hours. After centrifugation, washing, and drying, the mixture was heat-treated at 430-450℃ for 3-5 hours to form cerium oxide on the surface of diamond particles with deposited silicon carbide.
[0020] By adopting the above technical solution, diamond particles are graphitized at high temperature. Under vacuum conditions, the diamond surface becomes graphitized, forming a layer of highly active graphitic carbon. At a temperature exceeding the melting point of silicon powder, the silicon powder melts and evaporates in large quantities, forming highly active silicon vapor. The silicon vapor reacts with the carbon on the surface of the diamond particles to generate silicon carbide. As the reaction proceeds, the silicon carbide layer continuously thickens, eventually forming a dense silicon carbide protective layer with strong interfacial bonding on the surface of the diamond particles.
[0021] When heated, hexamethylenetetramine slowly hydrolyzes, releasing ammonia and causing the pH of the solution to rise uniformly. Cerium ions in the solution are uniformly precipitated on the surface of diamond particles deposited with silicon carbide in the form of cerium hydroxide or basic cerium carbonate. After heat treatment at 450℃, a nanoscale cerium oxide layer is formed on the silicon carbide layer.
[0022] Preferably, the high-strength buffer intermediate layer contains 3-5% ammonium bicarbonate and 1-2% silicon carbide.
[0023] By adopting the above technical solution, a certain amount of ammonium bicarbonate is added to the high-strength buffer interlayer. When heated, it decomposes to produce gas. Therefore, during the sintering process, these gases escape and leave pores in the originally dense high-strength buffer layer. After sound waves enter the open structure inside the material, they undergo friction and adhesion reactions with the pore walls, thereby producing the effect of increasing damping and attraction. However, the pores produced by ammonium bicarbonate will reduce the effective load-bearing area of the material and affect the bending strength and hardness of the interlayer. Silicon carbide is a high-strength, high-wear-resistant ceramic particle that can bear part of the load, pin grain boundaries, hinder dislocation movement, improve hardness and tensile strength, and strengthen the interlayer.
[0024] Preferably, the ammonium bicarbonate has a particle size of 50-100 μm.
[0025] By adopting the above technical solution, ammonium bicarbonate with the above particle size forms macropores after decomposition. Adjacent macropores are more likely to connect with each other, forming a three-dimensional open network, thus achieving better sound absorption and noise reduction effect.
[0026] Preferably, the mass ratio of ammonium bicarbonate to silicon carbide is 3:1.
[0027] By adopting the above technical solution, the above amounts of ammonium bicarbonate and silicon carbide can balance sound absorption and noise reduction with mechanical strength. During the sintering process, silicon carbide can act as a skeleton to guide the gas generated by the decomposition of ammonium bicarbonate to gather and escape around it, thereby promoting the connectivity of pores and helping to form an open-pore structure with better sound absorption.
[0028] Preferably, the diamond particles are arranged in a three-dimensional matrix in the working layer matrix powder, with a lateral spacing of 0.5mm-0.8mm and a longitudinal interlayer spacing of 0.6mm-1.0mm.
[0029] By adopting the above technical solution, the diamond particles are arranged in a three-dimensional matrix in an orderly manner within the matrix, avoiding the agglomeration or depletion caused by random distribution. This ensures that each diamond is subjected to uniform force, preventing premature breakage due to excessive impact load on a single diamond. Furthermore, it ensures that the lateral impact force applied by the cutting head to the stone surface during the cutting process is evenly distributed, thus eliminating corner chipping caused by local stress concentration. In addition, the orderly arrangement provides space for chip containment, and combined with the improvement of the matrix's hydrophilicity by titanium, cutting debris can be quickly carried away from the cutting arc area, greatly reducing frictional heat. The diamond particles are arranged in an orderly manner within the matrix powder of the working layer, ensuring uniform load distribution, preventing chipping, and avoiding the problems of insufficient spacing leading to particle accumulation, insufficient load on individual particles, and failure to cut. Conversely, excessive spacing can result in overloaded individual particles, which are prone to impact breakage. This orderly and uniform layout ensures that each diamond particle exerts equal cutting force into the stone, eliminating localized stress overload that can cause chipping and chipping. Furthermore, the orderly arrangement of diamond particles creates a three-dimensional chip-bearing network, allowing high-hardness rock powder generated during cutting to be discharged along the regular gaps, preventing powder from clogging the matrix surface, reducing the coefficient of friction between the cutter head and the stone, and ensuring consistently sharp and easy cutting. The spacing between the diamond particles also ensures sufficient width of the matrix metal between adjacent diamonds, anchoring each diamond and preventing a decrease in matrix strength due to overly dense particle density, as well as preventing excessive force on individual particles due to overly sparse particle density, which could lead to their removal.
[0030] Preferably, the diamond particles have a particle size of 80-140 mesh.
[0031] By adopting the above technical solution, diamond particles with a particle size of 80-140 mesh ensure that the diamond particles still have sufficient height to protrude from the matrix surface after hot pressing and sintering, enabling them to effectively plow the chips and leaving chip removal channels. The fine chips generated during cutting can be smoothly discharged along the tiny gaps without clogging the cutter head surface. Smooth chip removal reduces frictional heat and avoids softening or thermal cracking of the artificial stone resin components due to heat accumulation. In addition, the small particle size of 80-140 mesh diamond particles increases the number of diamonds distributed in the same area, reducing the cutting load borne by a single diamond particle. This allows the stress on the stone surface to be released along the grain boundaries in the form of micro-cracks, maintaining sharp edges while preventing grinding dulling.
[0032] Preferably, the thickness of the cutting head is 1mm-1.2mm.
[0033] Secondly, this application provides a method for preparing an ultra-sharp artificial stone cutting saw blade, employing the following technical solution: A method for preparing an ultra-sharp artificial stone cutting saw blade includes the following steps: According to the formula, copper powder, tin powder, cobalt powder, nickel powder, titanium powder and tungsten carbide are mixed evenly to obtain working layer matrix powder; iron powder, copper powder, nickel powder and cerium are mixed evenly to obtain intermediate layer powder; copper powder, tin powder, nickel powder and zinc powder are mixed evenly to make transition bottom layer powder. A microporous array template is used to embed diamond particles into the working layer matrix powder, so that the diamond particles are arranged in a three-dimensional matrix in the working layer matrix powder, and then cold-pressed to obtain the working layer blank. The intermediate layer powder and the transition bottom layer powder are sequentially laid on the working layer blank, and then cold-pressed to obtain a cold-pressed blank. The cutting head is obtained by vacuum hot pressing and sintering the cold-pressed billet; Using silver solder sheets with a silver content of 35-45%, the cutting head is brazed onto the silent substrate through high-frequency induction welding, and then the blade is sharpened to produce an ultra-sharp artificial stone cutting saw blade.
[0034] Preferably, the cold pressing pressure is 150-200 MPa and the holding time is 110-140 s.
[0035] Preferably, the sintering temperature of the vacuum hot pressing sintering is 760-790℃, the sintering pressure is 25-30MPa, and the holding time is 15-20min.
[0036] In summary, this application has the following beneficial effects: 1. Because this application uses a sintered body consisting of a sharp working outer layer, a high-strength buffer intermediate layer, and an easy-to-solder transition bottom layer as the cutting head, the high-strength buffer intermediate layer contains rare earth element cerium, which has excellent damping performance and can effectively block the transmission of vibration energy to the matrix, thus improving the cutting acoustic environment; the easy-to-solder transition bottom layer uses copper as the matrix, completely abandons iron and cobalt, and adds tin, nickel, and zinc. This system has low surface energy and can form good metallurgical intersolubility with silver-based brazing filler metal, reducing the wetting angle, allowing the solder to automatically spread and penetrate into the capillary gap, improving the weld strength and extending the service life of the saw blade.
[0037] 2. In this application, diamond particles with a particle size of 80-140 mesh are preferably used and arranged in an orderly manner in the working layer matrix powder. This can eliminate the single-particle overload caused by local agglomeration and the empty cutting friction caused by local depletion in random distribution, so that each diamond is subjected to uniform force, the cutting process is stable, and edge chipping and corner breakage are avoided. Moreover, the orderly arrangement and reserved regular gaps form a three-dimensional chip-bearing network, and the rock powder generated during cutting can be discharged from the cutting arc area in time, avoiding powder clogging of the matrix and frictional heating. At the same time, smooth chip discharge can keep the cutting resistance at a low level and improve the feed rate. Detailed Implementation
[0038] The following detailed description of the ultra-sharp artificial stone cutting saw blade of this application, in conjunction with specific embodiments, is intended to help those skilled in the art to have a more complete, accurate, and in-depth understanding of the inventive concept and technical solution of this application.
[0039] This application relates to an ultra-sharp artificial stone cutting saw blade, comprising a silent base and a plurality of cutting heads uniformly welded to the outer edge of the silent base. The silent base has a sandwich structure formed by a special steel sheet, a copper alloy sheet, and a special steel sheet. The special steel sheet and the copper alloy sheet are connected by spot welding. The copper alloy sheet has a thickness of 0.5 mm, and the special steel sheet has a thickness of 2 mm.
[0040] The silent base is circular, made of special steel sheets and copper alloy sheets into a disc shape with a predetermined diameter and thickness, and has a mounting hole in the center for mounting a drive shaft driven by a motor. Chip removal grooves are evenly spaced on the outer circumference of the silent base, and several cutting heads are welded to the outer circumference of the circular silent base by high-frequency welding process.
[0041] The thickness of the cutting head is 1.0-1.2mm. The cutting head is a sintered body consisting of an easy-to-weld transition bottom layer, a high-strength buffer intermediate layer, and a sharp working outer layer. The easy-to-weld transition bottom layer, the high-strength buffer intermediate layer, and the sharp working outer layer are arranged sequentially from the inside to the outside along a direction perpendicular to the surface of the silent substrate (i.e., parallel to the center circumference of the silent substrate).
[0042] The easy-to-solder transition layer strictly controls the content of iron and cobalt, with the core formula consisting of 70-75wt% copper powder, 10-15wt% tin powder, 5-10wt% nickel powder, and 10wt% zinc powder. This effectively reduces the wetting angle between the matrix and the silver solder sheet, significantly reduces the welding difficulty of subsequent high-frequency silver brazing, and improves the bonding strength.
[0043] The high-strength buffer layer does not contain diamond particles, but contains 50-60wt% iron powder, 20-30wt% copper powder, 10-19.5wt% nickel powder and 0.5wt% rare earth element cerium, which is used to absorb the high-frequency micro-vibrations generated when cutting brittle stone.
[0044] The sharp outer working layer is made of working layer matrix powder and 80-140 mesh high-strength diamond particles. This particle size range can ensure sufficient cutting height to expel rock powder while providing ultimate sharpness. The diamond particles are arranged in a three-dimensional matrix in the working layer matrix powder, with a lateral spacing of 0.5-0.8 mm and a longitudinal spacing of 0.6-1 mm between adjacent diamond particles. The working layer matrix powder contains 40-50 wt% copper powder, 10-15 wt% tin powder, 15-20 wt% cobalt powder, 10-15 wt% nickel powder, 2-5 wt% titanium powder, and 5-8 wt% tungsten carbide. This formula has excellent self-sharpening properties and can wear down synchronously with the 80-140 mesh diamond particles.
[0045] Example 1: An ultra-sharp artificial stone cutting blade, wherein the thickness of the cutting blade is 1.2mm, and the thickness ratio of the easy-to-weld transition bottom layer, the high-strength buffer middle layer and the sharp working outer layer is 1:2:7.
[0046] The solderable transition underlayer contains the following components by weight percentage: 70% copper powder, 10% tin powder, 10% nickel powder, and 10% zinc powder; The high-strength buffer interlayer contains the following components by weight percentage: 60% iron powder, 25% copper powder, 14.5% nickel powder and 0.5% cerium; The sharp working outer layer is made of working layer matrix powder and diamond particles distributed in a three-dimensional matrix in the working layer matrix powder. The working layer matrix powder contains the following components by mass percentage: 45% copper powder, 15% tin powder, 15% cobalt powder, 15% nickel powder, 5% titanium powder and 5% tungsten carbide. The volume fraction of diamond particles in the sharp working outer layer is 12%, and the particle size of the diamond particles is 100 / 120 mesh.
[0047] Example 2: An ultra-sharp artificial stone cutting saw blade, wherein the thickness of the cutting head is 1.2mm, and the thickness ratio of the easy-to-weld transition bottom layer, the high-strength buffer middle layer and the sharp working outer layer is 1:2:7.
[0048] The solderable transition underlayer contains the following components by weight percentage: 75% copper powder, 10% tin powder, 5% nickel powder, and 10% zinc powder; The high-strength buffer interlayer contains the following components by weight percentage: 54.5% iron powder, 30% copper powder, 15% nickel powder and 0.5% cerium; The sharp working outer layer is made of working layer matrix powder and diamond particles distributed in a three-dimensional matrix in the working layer matrix powder. The working layer matrix powder contains the following components by mass percentage: 50% copper powder, 10% tin powder, 20% cobalt powder, 10% nickel powder, 2% titanium powder and 8% tungsten carbide. The volume fraction of diamond particles in the sharp working outer layer is 15%, and the particle size of the diamond particles is 100 / 120 mesh.
[0049] Example 3: An ultra-sharp artificial stone cutting saw blade, wherein the thickness of the cutting head is 1.2mm, and the thickness ratio of the easy-to-weld transition bottom layer, the high-strength buffer middle layer and the sharp working outer layer is 1:2:7.
[0050] The solderable transition underlayer contains the following components by weight percentage: 70% copper powder, 12% tin powder, 8% nickel powder, and 10% zinc powder; The high-strength buffer interlayer contains the following components by weight percentage: 60% iron powder, 29.5% copper powder, 10% nickel powder, and 0.5% cerium; The sharp working outer layer is made of working layer matrix powder and diamond particles distributed in a three-dimensional matrix in the working layer matrix powder. The working layer matrix powder contains the following components by mass percentage: 43% copper powder, 13% tin powder, 18% cobalt powder, 13% nickel powder, 5% titanium powder and 8% tungsten carbide. The volume fraction of diamond particles in the sharp working outer layer is 10%, and the particle size of the diamond particles is 100 / 120 mesh.
[0051] Example 4: An ultra-sharp artificial stone cutting saw blade, which differs from Example 1 in that the volume fraction of diamond particles in the sharp working outer layer is 5%.
[0052] Example 5: An ultra-sharp artificial stone cutting saw blade, which differs from Example 1 in that the volume fraction of diamond in the sharp working outer layer is 20%.
[0053] Example 6: An ultra-sharp artificial stone cutting saw blade, which differs from Example 1 in that the thickness ratio of the easy-to-weld transition bottom layer, the high-strength buffer middle layer, and the sharp working outer layer is 2:1:7.
[0054] Example 7: An ultra-sharp artificial stone cutting saw blade, which differs from Example 1 in that the thickness ratio of the easy-to-weld transition bottom layer, the high-strength buffer middle layer, and the sharp working outer layer is 1:2:3.
[0055] Example 8: An ultra-sharp artificial stone cutting saw blade, which differs from Example 1 in that the thickness ratio of the easy-to-weld transition bottom layer, the high-strength buffer middle layer, and the sharp working outer layer is 1:1:8.
[0056] The preparation method of the ultra-sharp artificial stone cutting saw blades in Examples 1-8 includes the following steps: Digital image processing technology is used to scan diamond particles, with micrometers as the unit of measurement. The minimum area limit of the smallest diamond particle is measured and set to accurately filter dust and tiny impurities. S1. According to the above proportions, copper powder, tin powder, nickel powder and zinc powder are mixed evenly to obtain the transition bottom layer powder; according to the above proportions, iron powder, copper powder, nickel powder and cerium are mixed evenly to obtain the intermediate layer powder; according to the above proportions, copper powder is mixed evenly with tin powder, cobalt powder, nickel powder, titanium powder and tungsten carbide to obtain the working layer matrix powder. S2. Using a microporous array template adapted to diamond particles with a particle size of 100 / 120 mesh, diamond particles are implanted into the working layer matrix powder, so that the diamond particles are arranged in a three-dimensional matrix in the working layer matrix powder. The lateral spacing between adjacent diamond particles in the working layer matrix powder is 0.6 mm, and the longitudinal spacing is 0.6 mm. The working layer blank is obtained by cold pressing at 160 MPa. S3. The intermediate layer powder and the transition bottom layer powder are sequentially laid on the working layer blank, and then cold-pressed at 180MPa to obtain the cold-pressed blank. S4. Place the cold-pressed blank in a vacuum sintering furnace, heat it to 780℃ and apply a pressure of 28MPa, hold it at the temperature and pressure for 15 minutes, and sinter it to obtain a cutting head with a thickness of 1.2mm. S5. Using silver solder with a silver content of 35% as the brazing material, the cutting head is welded to the outer circumference of the silent substrate through high-frequency silver brazing process, and then subjected to high-frequency sharpening treatment by silicon carbide grinding wheel to obtain an ultra-sharp artificial stone cutting saw blade.
[0057] Example 9: An ultra-sharp artificial stone cutting saw blade, differing from Example 1 in that, in step S2, before the diamond particles are implanted into the working layer matrix powder, a silicon carbide layer and a cerium oxide layer are sequentially deposited on its surface. The specific method is as follows: Diamond particles were placed in a vacuum sintering furnace for surface graphitization treatment. The temperature was first raised to 800°C at a rate of 30°C / min, then raised to 1500°C at a rate of 20°C / min, and then raised to 1600°C at a rate of 10°C / min. The temperature was then held under vacuum without pressure for 15 minutes to obtain diamond / graphite composite particles. Diamond / graphite composite particles were placed in a graphite cavity filled with silicon powder and fixed 8 mm above the silicon powder. The graphite cavity was then moved into a vacuum furnace and heated to 1700°C at a heating rate of 8°C / min. The vacuum degree was set to 1 Pa and held for 30 min. The furnace was then cooled to room temperature to obtain diamond particles with deposited silicon carbide. Deionized water and anhydrous ethanol were mixed in a 1:1 mass ratio to prepare 1000 mL of dispersion. 5 g of diamond particles deposited with silicon carbide were added, stirred for 30 min, and sonicated for 120 min to obtain a suspension. Add 5g of cerium nitrate to the suspension, add hexamethylenetetramine solution (prepared by 1.6g of hexamethylenetetramine and 500mL of deionized water), adjust the pH to 7 with sodium hydroxide solution, heat and stir in a water bath at 75℃ for 2h, centrifuge, wash, dry, and heat treat at 450℃ for 3h to form cerium oxide on the surface of diamond particles with deposited silicon carbide.
[0058] Example 10: An ultra-sharp artificial stone cutting saw blade, differing from Example 1 in that, in step S2, before the diamond particles are implanted into the working layer matrix powder, a silicon carbide layer is deposited on its surface. The specific method is as follows: Diamond particles were placed in a vacuum sintering furnace for surface graphitization treatment. The temperature was first raised to 800°C at a rate of 30°C / min, then raised to 1500°C at a rate of 20°C / min, and then raised to 1600°C at a rate of 10°C / min. The temperature was then held under vacuum without pressure for 15 minutes to obtain diamond / graphite composite particles. Diamond / graphite composite particles were placed in a graphite cavity filled with silicon powder and fixed 8 mm above the silicon powder. The graphite cavity was then moved into a vacuum furnace and heated to 1700°C at a heating rate of 8°C / min. The vacuum degree was set to 1 Pa and held for 30 min. The furnace was then cooled to room temperature to obtain diamond particles with deposited silicon carbide.
[0059] Example 11: An ultra-sharp artificial stone cutting saw blade, differing from Example 1 in that, in step S2, before the diamond particles are implanted into the working layer matrix powder, a cerium oxide layer is deposited on its surface. The specific method is as follows: Deionized water and anhydrous ethanol were mixed in a 1:1 mass ratio to obtain 1000 mL of dispersion. 5 g of diamond particles were added, stirred for 30 min, and sonicated for 120 min to obtain a suspension. Add 5g of cerium nitrate to the suspension, add hexamethylenetetramine solution (prepared by 1.6g of hexamethylenetetramine and 500mL of deionized water), adjust the pH to 7 with sodium hydroxide solution, heat and stir in a water bath at 75℃ for 2h, centrifuge, wash, dry, and heat treat at 450℃ for 3h to form cerium oxide on the surface of diamond particles.
[0060] Example 12: An ultra-sharp artificial stone cutting saw blade, differing from Example 1 in that the high-strength buffer intermediate layer contains the following components by mass percentage: 25% copper powder, 14.5% nickel powder, 0.5% cerium, 3% ammonium bicarbonate and 1% silicon carbide, with the balance being iron powder. The ammonium bicarbonate has a particle size of 100 μm, and the silicon carbide has a particle size of 120 μm. The iron powder, copper powder, nickel powder, ammonium bicarbonate, silicon carbide and cerium are mixed evenly to obtain the intermediate layer powder.
[0061] Example 13: An ultra-sharp artificial stone cutting saw blade, differing from Example 1 in that the high-strength buffer intermediate layer contains the following components by mass percentage: 25% copper powder, 14.5% nickel powder, 0.5% cerium, 5% ammonium bicarbonate and 2% silicon carbide, with the balance being iron powder. The ammonium bicarbonate has a particle size of 100 μm, and the silicon carbide has a particle size of 120 μm. The iron powder, copper powder, nickel powder, ammonium bicarbonate, silicon carbide and cerium are mixed evenly to obtain the intermediate layer powder.
[0062] Example 14: An ultra-sharp artificial stone cutting saw blade, which differs from Example 1 in that the high-strength buffer intermediate layer contains the following components by mass percentage: 25% copper powder, 14.5% nickel powder, 0.5% cerium, 4% ammonium bicarbonate, with the balance being iron powder. The ammonium bicarbonate has a particle size of 100 μm. The iron powder, copper powder, nickel powder, ammonium bicarbonate, and cerium are mixed evenly to obtain the intermediate layer powder.
[0063] Example 15: An ultra-sharp artificial stone cutting saw blade, which differs from Example 1 in that the high-strength buffer intermediate layer contains the following components by mass percentage: 25% copper powder, 14.5% nickel powder, 0.5% cerium, 4% silicon carbide, with the balance being iron powder. The silicon carbide has a particle size of 120μm. The iron powder, copper powder, nickel powder, silicon carbide, and cerium are mixed evenly to obtain the intermediate layer powder.
[0064] Example 16: An ultra-sharp artificial stone cutting saw blade, differing from Example 1 in that the high-strength buffer layer contains the following components by mass percentage: 25% copper powder, 14.5% nickel powder, 0.5% cerium, 3% ammonium bicarbonate and 1% silicon carbide, with the balance being iron powder. The ammonium bicarbonate has a particle size of 100 μm, and the silicon carbide has a particle size of 120 μm. The iron powder, copper powder, nickel powder, ammonium bicarbonate, silicon carbide and cerium are mixed evenly to obtain the intermediate layer powder. Furthermore, a silicon carbide layer and a cerium oxide layer are sequentially deposited on the surface of the diamond particles, using the same method as in Example 9.
[0065] Comparative Example Comparative Example 1: An ultra-sharp artificial stone cutting saw blade, which differs from Example 1 in that the sharp working outer layer is made of a mixture of working matrix powder and diamond particles, and is not arranged in an orderly manner using a microporous array template. The rest of the process is the same as that of Example 1.
[0066] Comparative Example 2: An ultra-sharp artificial stone cutting saw blade, which differs from Example 1 in that the diamond particles have a particle size of 60 mesh.
[0067] Comparative Example 3: An ultra-sharp artificial stone cutting saw blade, which differs from Example 1 in that the easy-to-weld transition underlayer contains the following components by weight percentage: 70% copper powder and 30% nickel powder.
[0068] Comparative Example 4: An ultra-sharp artificial stone cutting saw blade, which differs from Example 1 in that the easy-to-solder transition underlayer contains the following components by weight percentage: 80% iron powder, 10% tin powder and 10% nickel powder.
[0069] Comparative Example 5: An ultra-sharp artificial stone cutting saw blade, which differs from Example 1 in that the high-strength buffer intermediate layer contains the following components by weight percentage: 60% iron powder, 25% copper powder and 15% nickel powder.
[0070] Comparative Example 6: An ultra-sharp artificial stone cutting saw blade, which differs from Example 1 in that the working layer matrix powder contains the following components by weight percentage: 50% copper powder, 15% tin powder, 15% cobalt powder, 15% nickel powder and 5% titanium powder.
[0071] Comparative Example 7: An ultra-sharp artificial stone cutting saw blade, which differs from Example 1 in that the working layer matrix powder contains the following components by weight percentage: 55% copper powder, 15% tin powder, 15% cobalt powder and 15% nickel powder.
[0072] Comparative Example 8: An ultra-sharp artificial stone cutting saw blade, which differs from Example 1 in that it does not have an easy-to-weld transition bottom layer, and the cutting head is a sintered body of a high-strength buffer intermediate layer and a sharp working outer layer with a thickness ratio of 3:7.
[0073] Comparative Example 9: An ultra-sharp artificial stone cutting saw blade, which differs from Example 1 in that it does not have a high-strength buffer intermediate layer, and the cutting head is a sintered body of a 3:7 easy-to-weld transition bottom layer and a sharp working outer layer.
[0074] Performance testing The D350 saw blades for high-density ceramic slabs with a thickness of 15 mm were prepared according to the above method, and the performance was tested according to the following method. The test results are recorded in Table 2.
[0075] 1. Torque value: The torque wrench is used for testing. The saw blade to be tested is placed on the central shaft that matches its specifications and placed horizontally on the test table. The saw blade base is fixed with a cover plate or special clamp and placed to rotate during the test. The jaws of the torque wrench are clamped onto the single blade to be tested. Then, the handle of the wrench is held and the force is applied evenly in both upward and downward directions until the blade is dislodged from the base (tooth is lost). The torque value is recorded. Ten blades are tested on each saw blade, and five saw blades are tested in each embodiment or comparative example. The test results are averaged.
[0076] 2. Impact toughness: The impact toughness is tested in accordance with GB / T 5318-1985 "Sintered Metal Materials (excluding cemented carbide) Unnotched Impact Test Specimens".
[0077] 3. Bending strength: The bending strength shall be tested in accordance with GB / T5319-2002 "Determination of transverse fracture strength of sintered metallic materials (excluding cemented carbide)".
[0078] 4. Cutting test: Set the cutting speed to 2800 r / min and the feed speed to 4 m / min. Perform continuous or intermittent cutting on a 15 mm thick and 100 m long high-density rock slab until the saw blade wears down to the point where it can no longer cut effectively or the kerf width exceeds the tolerance range. During this period, test the current during the cutting process; stop the machine periodically, measure the radial wear of the cutter head, and calculate the wear rate per unit cutting length.
[0079] During the cutting process, observe whether there are chipped edges or corners on the cut surface. Take 10 test points on the cut surface of a 100m long high-density rock slab, with each test point 10m apart. Use a surface roughness meter to measure the roughness of the test points and take the average value.
[0080] During the cutting process, 10 operators scored the noise, the smoothness of the cutting process, and the presence of chipped edges. The scoring criteria are shown in Table 1, and the average score was taken.
[0081] Table 1
[0082] Table 2
[0083] As can be seen from the data in Table 2, the cutting saw blades obtained by the methods in Examples 1-3 of this application have high sharpness and good chip removal effect, smooth cutting, high impact toughness and bending strength, less power consumption, and greatly reduced cutting noise. The cut is straight and the weld is firm.
[0084] Compared to Example 1, Examples 4 and 5 respectively reduced and increased the amount of diamond particles added to the sharp working outer layer. It can be seen that the impact toughness and bending strength of the saw blade made in Example 4 decreased, and the wear rate of the saw blade increased after cutting. Although the saw blade made in Example 5 has a lower wear rate, it consumes more energy, produces more noise, and has a reduced cutting smoothness during cutting.
[0085] Compared with Example 1, Example 6 increases the thickness of the easy-to-weld transition layer, Example 7 decreases the thickness of the sharp working outer layer, and Example 8 increases the thickness of the sharp working outer layer but decreases the thickness of the easy-to-weld transition layer. The torsional value of the saw blade prepared in Example 6 is not much different from that in Example 1, indicating that increasing the thickness of the layer has little effect on the weld strength of the blade head. The impact toughness and bending strength of the blade head prepared in Example 7 are reduced, and the impact energy and wear resistance of the saw blade prepared in Example 8 are reduced.
[0086] Compared with Example 1, Example 9 uses silicon carbide and cerium oxide to be deposited sequentially on the surface of diamond particles. It can be seen that the cutter head prepared in Example 9 has a smaller surface roughness and higher impact toughness after cutting the stone. There are no continuous notches on the upper and lower edges, and it is not easy to break.
[0087] Compared with Example 1, Examples 10 and 11 deposited silicon carbide and cerium oxide layers on diamond particles, respectively. Compared with Example 9, the cutter head prepared in Example 10 had an increased wear rate, decreased impact toughness and bending strength, while the cutter head prepared in Example 11 still had a relatively small surface roughness after cutting stone. This indicates that the silicon carbide and cerium oxide layers can improve the stability of diamond particles in the matrix material, improve hardness, increase cutting smoothness, and improve the quality of the cutting surface.
[0088] Compared with Example 1, Examples 12 and 13 added ammonium bicarbonate and silicon carbide to the high-strength buffer intermediate layer. As shown in Table 2, the cutter heads prepared in Examples 12 and 13 have good sound absorption and noise reduction effects and high bending strength. In contrast, Examples 14 and 15 only added ammonium bicarbonate and silicon carbide alone. It can be seen that Example 14 has a higher noise score and better sound absorption and noise reduction effect, but a higher wear rate, and a decrease in bending strength and impact toughness. Example 15 has a lower noise score and higher cutting noise, but a lower wear rate, stronger wear resistance, and higher impact toughness than Example 1. This shows that adding ammonium bicarbonate and silicon carbide in combination to the intermediate layer can not only increase the bending strength of the cutter head, but also improve the sound absorption and noise reduction ability of the cutter head, while adding either one alone cannot achieve this effect.
[0089] Compared with Example 1, Example 16 not only deposits a silicon carbide layer and a cerium oxide layer sequentially on the surface of diamond particles, but also adds ammonium bicarbonate and silicon carbide in the intermediate layer. As can be seen from the data in Table 2, compared with Example 9 and Example 12, the cutter head prepared in Example 16 not only has higher impact toughness and bending strength, but also stronger sound absorption and noise reduction capabilities, and is less prone to edge chipping.
[0090] Compared with Example 1, Comparative Example 1, which did not use diamond particles arranged in a three-dimensional matrix, produced saw blades that produced obvious sparks during cutting, and the cut surfaces of the plates were severely chipped.
[0091] In Comparative Example 2, the particle size of the diamond particles was increased. As can be seen from the data in Table 2, compared with Example 1, the noise during cutting was greater and the edge showed more severe chipping defects, which could not meet the cutting requirements.
[0092] Compared with Example 1, only copper and nickel were used in Comparative Example 3, and iron powder was used to replace zinc and copper in Comparative Example 4. The data in Table 1 show that the torque value of the saw blades prepared in Comparative Example 3 and Comparative Example 4 decreased significantly, and the weld strength between them and the substrate decreased.
[0093] Compared to Example 1, Comparative Example 5 did not add rare earth element cerium to the high-strength buffer intermediate layer, resulting in a saw blade with higher noise and reduced smoothness.
[0094] Compared with Example 1, Comparative Example 6 uses copper powder instead of tungsten carbide, while Comparative Example 7 uses copper powder instead of tungsten carbide and titanium powder. It can be seen that the saw blades prepared in Comparative Example 6 and Comparative Example 7 have increased wear rate, weakened wear resistance, and are prone to breakage defects during cutting.
[0095] Compared with Example 1, Comparative Examples 8 and 9 did not have an easy-to-weld transition underlayer and a high-strength buffer intermediate layer, respectively. It can be seen that the saw blade torque value obtained by Comparative Example 8 decreased and the weld strength was weakened, while the saw blade obtained by Comparative Example 9 had greater noise during cutting.
[0096] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. An ultra-sharp artificial stone cutting saw blade, characterized in that, It includes a silent substrate and several cutting heads uniformly welded to the outer edge of the silent substrate. The silent substrate is a sandwich structure of special steel sheet-copper alloy sheet-special steel sheet. The cutting head is a sintered body consisting of a weldable transition bottom layer, a high-strength buffer intermediate layer, and a sharp working outer layer. The weldable transition bottom layer, the high-strength buffer intermediate layer, and the sharp working outer layer are arranged sequentially from the inside to the outside along a direction perpendicular to the surface of the silent substrate. The weldable transition bottom layer is in contact with the surface of the silent substrate. The solderable transition underlayer comprises, by weight percentage, 70-75% copper powder, 10-15% tin powder, 5-10% nickel powder, and 10% zinc powder; The high-strength buffer intermediate layer comprises, by weight percentage, 20-30% copper powder, 10-19.5% nickel powder, 0.5% cerium, and the remainder is iron powder; The sharp working outer layer is made of working layer matrix powder and diamond particles. The working layer matrix powder, by mass percentage, includes 40-50% copper powder, 10-15% tin powder, 15-20% cobalt powder, 10-15% nickel powder, 2-5% titanium powder, and 5-8% tungsten carbide.
2. The ultra-sharp artificial stone cutting saw blade according to claim 1, characterized in that: The thickness ratio of the easy-to-solder transition base layer, the high-strength buffer intermediate layer, and the sharp working outer layer is 1:2:
7.
3. The ultra-sharp artificial stone cutting saw blade according to claim 1, characterized in that: The volume fraction concentration of the diamond particles in the sharp working outer layer is 10-15%.
4. The ultra-sharp artificial stone cutting saw blade according to claim 1, characterized in that: The diamond particles are sequentially deposited with a silicon carbide layer and a cerium oxide layer.
5. The ultra-sharp artificial stone cutting saw blade according to claim 1, characterized in that: The high-strength buffer intermediate layer also contains 3-5% ammonium bicarbonate and 1-2% silicon carbide.
6. The ultra-sharp artificial stone cutting saw blade according to claim 1, characterized in that: The diamond particles are arranged in a three-dimensional matrix in the working layer matrix powder, with a lateral spacing of 0.5mm-0.8mm and a longitudinal spacing of 0.6mm-1.0mm.
7. The ultra-sharp artificial stone cutting saw blade according to claim 1, characterized in that: The diamond particles have a particle size of 80-140 mesh.
8. The ultra-sharp artificial stone cutting saw blade according to claim 1, characterized in that: The thickness of the cutter head is 1mm-1.2mm.
9. The method for preparing the ultra-sharp artificial stone cutting saw blade according to any one of claims 1-8, characterized in that, Includes the following steps: According to the formula, copper powder, tin powder, cobalt powder, nickel powder, titanium powder and tungsten carbide are mixed evenly to obtain working layer matrix powder; iron powder, copper powder, nickel powder and cerium are mixed evenly to obtain intermediate layer powder; copper powder, tin powder, nickel powder and zinc powder are mixed evenly to make transition bottom layer powder. A microporous array template is used to embed diamond particles into the working layer matrix powder, so that the diamond particles are arranged in a three-dimensional matrix in the working layer matrix powder, and then cold-pressed to obtain the working layer blank. The intermediate layer powder and the transition bottom layer powder are sequentially laid on the working layer blank, and then cold-pressed to obtain a cold-pressed blank. The cutting head is obtained by vacuum hot pressing and sintering the cold-pressed billet; Using silver solder sheets with a silver content of 35-45%, the cutting head is brazed onto the silent substrate through high-frequency induction welding, and then the blade is sharpened to produce an ultra-sharp artificial stone cutting saw blade.
10. The method for preparing the ultra-sharp artificial stone cutting saw blade according to claim 9, characterized in that, The cold pressing pressure is 150-200MPa, and the holding time is 110-140s; The sintering temperature of the vacuum hot pressing sintering is 760-790℃, the sintering pressure is 25-30MPa, and the holding time is 15-20min.
